Optimal Evacuation Plan Design with IP-Solver - Janacek, Jaroslav; Sibila, Michal (Communications - Scientific Letters of the University of Zilina, 2009)
This paper deals with two different computer-supported approaches to an evacuation plan design, which should assign the available vehicles to endangered dwelling places so that the total time of evacuation is minimal. It is assumed that some safe place is pre-assigned to each endangered dwelling place and there are determined locations of homogenous fleets of available vehicles, which can be used for transport of the endangered population from their dwelling places to the pre-assigned places. In this paper, we suggest and compare two approaches to the evacuation plan design. The first approach assigns all vehicles of a fleet to one evacuated dwelling place and the second one enables to assign individually any part of a fleet to the dwelling places.
Keywords: no keywords